2017
DOI: 10.3390/su10010057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Building Design Elements on Residential Thermal Environment

Abstract: Abstract:Residential thermal environment affects the life of residents in terms of their physical and mental health. Many studies have shown that building design elements affect the urban thermal environment. In this study, Nanjing City was used as the study area. A three-dimensional microclimate model was used to simulate and analyze the effects of four main factors, namely, building height, density, layout and green ratio, on thermal environment in residential areas. Results showed that 25% building density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…They showed that indoor wind in the upper floor is almost four times higher than in the lower floor. Other researchers investigated the effect of building height on outdoor thermal comfort during the daytime in order to mitigate heat stress in summer [59,60]. However, although several conclusions may be applied to other cases, the results of each one represents a specific context.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that indoor wind in the upper floor is almost four times higher than in the lower floor. Other researchers investigated the effect of building height on outdoor thermal comfort during the daytime in order to mitigate heat stress in summer [59,60]. However, although several conclusions may be applied to other cases, the results of each one represents a specific context.…”
Section: Introductionmentioning
confidence: 99%
“…[8] This model requires two main input files, including the configuration file containing settings for initialization values and timings and the 3D model file designing the spatial location, height of buildings, vegetation and soils based on a cell in the simulated area. [9,10] The four steps are described below:…”
Section: Methodsmentioning
confidence: 99%
“…The main evaluation indices of the urban thermal environment are atmospheric temperature (T a ), land surface temperature and thermal comfort. Among them, T a and land surface temperature are utilized more in analyzing the spatial distribution of difference of temperature [50]. The impact of vegetation types on air and surface temperatures are researched [51,52] because vegetation and surface temperature interact.…”
Section: The Heat Impactmentioning
confidence: 99%
“…The thermal environment problem has attracted significant attention with the progress of urbanization [61,62] and it has received extensive attention from scholars for both the indoor and outdoor thermal environment [50,[62][63][64][65]. The internal heat source at UCG influences the temperature field in the overburden.…”
Section: Mathematical Model For Two-dimensional (2d) Temperature Fieldsmentioning
confidence: 99%